2006
DOI: 10.1007/s00259-006-0240-1
|View full text |Cite
|
Sign up to set email alerts
|

MIBG-SPECT/CT-angiography with 3-D reconstruction of an extra-adrenal phaeochromocytoma with dissection of an aortic aneurysm

Abstract: Phaeochromocytomas can cause severe complications like stroke, lung oedema, myocardial infarction or aortic dissection. Ten percent of phaeochromocytomas originate in extra-adrenal localisations and can be detected with 123 I-MIBG scintigraphy [1]. We report on a 50-year-old patient with weight loss, night sweating and increased urinary noradrenaline levels. SPECT with 358 MBq 123 I-MIBG and additionally a dual-phase diagnostic CT were performed, showing increased MIBG uptake para-aortally on the left side (a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…However some authors have suggested a role for MIBG in the presence of genetic mutations with increased malignant potential (192). (193)(194)(195)(196)(197)(198)(199)(200)(201). One study found SPECT/CT had incremental diagnostic value over planar scintigraphy in up to 53% of cases (202).…”
Section: Advantages Of Spect/ct (Refs) Comments and Findingsmentioning
confidence: 95%
“…However some authors have suggested a role for MIBG in the presence of genetic mutations with increased malignant potential (192). (193)(194)(195)(196)(197)(198)(199)(200)(201). One study found SPECT/CT had incremental diagnostic value over planar scintigraphy in up to 53% of cases (202).…”
Section: Advantages Of Spect/ct (Refs) Comments and Findingsmentioning
confidence: 95%